Anti-Diarrhoeal Activity of Azanza garckeana Fruit Aqueous Extract Using Swiss Mice - Benjamin Ogunma Gabriel; Grace Nonye Ifechukwude; Innocent Inomo Inomo; Ofunre Ozolua Eboreime; Evonamhe Emmanuel Oloruntoba; MacDonald Idu (Darul Yasin Al Sys, 2026)
Traditional medicine encompasses medical therapies, methods, theories, and practices that employ products derived from plants, animals, and minerals, as well as spiritual and manual therapies and exercises. This study aimed to evaluate the antidiarrheal potential of Azanza garckeana in Swiss mice. Different doses of the plant extract (25, 50, and 100 mg/kg) were assessed using castor oil–induced diarrhea and gastrointestinal transit models. The results showed that the extract produced a significant (p < 0.05) reduction in the frequency of defecation of wet feces and in total fecal output compared with the control group. At higher doses, the extract also elicited significant (p < 0.05) antimotility effects relative to untreated controls. These findings validate the ethnomedicinal use of Azanza garckeana as an effective antidiarrheal agent and indicate the need for further studies on compound isolation, characterization, and pharmacological evaluation.